2020
DOI: 10.3390/plants9040422
|View full text |Cite
|
Sign up to set email alerts
|

Role and Regulation of Cytokinins in Plant Response to Drought Stress

Abstract: Cytokinins (CKs) are key phytohormones that not only regulate plant growth and development but also mediate plant tolerance to drought stress. Recent advances in genome-wide association studies coupled with in planta characterization have opened new avenues to investigate the drought-responsive expression of CK metabolic and signaling genes, as well as their functions in plant adaptation to drought. Under water deficit, CK signaling has evolved as an inter-cellular communication network which is essential to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 150 publications
(233 reference statements)
3
84
0
Order By: Relevance
“…Our studies based on employing the SARK or the MT promoter fused to the IPT gene clearly demonstrated positive effect on growth and biomass production under abiotic stresses in model plants such as Arabidopsis and tobacco as well in major crops such as rice, wheat, cotton, etc. (see Gujjar and Supaibulwatana, 2019;Hai et al, 2020). Similar positive regulation of drought stress by CKs has been reported also for transgenic plants containing the SAG12 promoter fused to the IPT gene (Merewitz et al, 2010;Zhang et al, 2010).…”
Section: Reprograming Of Gene Expression In the Cks Overproducing Plasupporting
confidence: 73%
See 2 more Smart Citations
“…Our studies based on employing the SARK or the MT promoter fused to the IPT gene clearly demonstrated positive effect on growth and biomass production under abiotic stresses in model plants such as Arabidopsis and tobacco as well in major crops such as rice, wheat, cotton, etc. (see Gujjar and Supaibulwatana, 2019;Hai et al, 2020). Similar positive regulation of drought stress by CKs has been reported also for transgenic plants containing the SAG12 promoter fused to the IPT gene (Merewitz et al, 2010;Zhang et al, 2010).…”
Section: Reprograming Of Gene Expression In the Cks Overproducing Plasupporting
confidence: 73%
“…This observation suggested that the phenomenon of CK-induced delayed senescence is also accompanied by an additional advantage of enhanced drought resistance and allowed us to suggest a novel technology for the development of drought-resistant plants ( Gepstein et al, 2017 ). Since then, major crops, including rice, wheat, peanut, cotton etc, have been developed to overexpress CKs under stress conditions (see Hai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokinins (CK) are N6-substituted adenine derivatives which are originally defined as a key regulator participating in various plant developmental activities, including organ formation, apical dominance, and leaf senescence (El-Showk et al, 2013). Nowadays, increasing evidence also indicates the action of cytokinin in response to stresses (Hai et al, 2020). A recent cytokinin-responsive transcriptome analysis in rice revealed that a large number of genes are involved in both biotic and abiotic stresses (Raines et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that AHK2, AHK3, and AHK4 are negative regulators of dehydration and salt tolerance, and the ahk2 and ahk3 mutants displayed higher survival rates under severe water deprivation (Tran et al, 2007;Kang et al, 2012). However, some studies found that cytokinin could also function as a positive regulator in drought stress adaptation (Hai et al, 2020). For example, the ectopic expression of the isopentenyltransferase gene (IPT) that encodes a rate-limiting enzyme in cytokinin biosynthesis increases endogenous cytokinin levels as well as improves drought stress tolerance in transgenic cotton (Kuppu et al, 2013), creeping bentgrass (Xu et al, 2016), eggplant (Xiao et al, 2017), and tropical maize (Leta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%